In Vitro Antibacterial Activity of Some New Unsymmetrical Pentacoordinate Cobalt (III) Schiff Base Complexes - yousof mardani; sheida esmaielzadeh (شیمی کاربردی روز, 2018)
Four new penta-coordinated cobalt (III) complexes of general formulae [CoL1-4]ClO4.H2O (where L1= methyl-2-{[1-methyl-2-(2-hydroxyphenyl)methylidynenitrilo]ethyl}-amino-1-cyclopenteneithiocarboxylate, (H2cdsalMeen), L2=methyl-2-{[1-methyl-2-(2-hydroxy-5-clorophenyl)methylidynenitrilo]ethyl}amino-1-cyclopentenedithiocarboxylate, (H2cd5ClsalMeen), L3=methyl-2-{[1-methyl-2-(2-hydroxy-5-bromophenyl)methylidynenitrilo]ethyl}amino-1-cyclopent-enedithiocarboxylate, (H2cd5BrsalMeen), L4=methyl-2-{[1-methyl-2-(2-hydroxy-5-nitrophenyl)methylidynenitrilo]ethyl}amino-1-cyclopentenedithiocarboxylate, (H2cd5NO2salMeen)) were synthesized and characterized by different physico-chemical techniques. The spectroscopic data confirmed the structure of penta-coordinated complexes. The Schiff base ligands coordinated to the cobalt ion through the phenolic oxygen, the both azomethine nitrogen atoms and the sulfur of C-S group acting tetradentate behaviour and the axial donor atom from a tributylphosphin P atom is as a five coordinate. From the elemental analysis data, the stoichiometry of the complexes 1:1 (metal:ligand) was ascertained. Antibacterial activities of the prepared compounds were evaluated in vitro against Staphylococcus aureus and Escherichia Coli. Their minimum inhibitory concentration (MIC) and maximum bactericidal concentration (MBC) for all synthesized ligands and their cobalt (III) complexes were determined. The ligands and their complexes exhibited significant antibacterial activity. The free ligands showed high activities compared with the CoIII complexes.